Survival and reproduction in Arctic caribou are associated with summer forage and insect harassment - Johnson, Heather E.; Lenart, Elizabeth A.; Gustine, David D.; Adams, Layne G.; Barboza, Perry S. (Frontiers in Ecology and Evolution, 2022)
Investigators have speculated that the climate-driven ‘greening of the Arctic’ may benefit barren-ground caribou populations, but paradoxically many populations have declined in recent years. This pattern has raised concerns about the influence of summer habitat conditions on caribou demographic rates, and how populations may be impacted in the future. The short Arctic summer provides caribou with important forage resources but is also the time they are exposed to intense harassment by insects, factors which are both being altered by longer, warmer growing seasons. To better understand the effects of summer forage and insect activity on Arctic caribou demographic rates, we investigated the influence of estimated forage biomass, digestible energy (DE), digestible nitrogen (DN), and mosquito activity on the reproductive success and survival of adult females in the Central Arctic Herd on the North Slope of Alaska. We tested the hypotheses that greater early summer DN would increase subsequent reproduction (parturition and late June calving success) while greater biomass and DE would increase adult survival (September-May), and that elevated mosquito activity would reduce both demographic rates. Because the period when abundant forage DN is limited and overlaps with the period of mosquito harassment, we also expected years with low DN and high harassment to synergistically reduce caribou reproductive success. Examining these relationships at the individual-level, using GPS-collared females, and at the population-level, using long-term monitoring data, we generally found support for our expectations. Greater early summer DN was associated with increased subsequent calving success, while greater summer biomass was associated with increased adult survival. Mosquito activity was associated with reductions in adult female parturition, late June calving success, and survival, and in years with low DN, had compounding effects on subsequent late June calving success. Our findings indicate that summer nutrition and mosquito activity collectively influence the demographic rates of Arctic caribou, and may impact the dynamics of populations in the future under changing environmental conditions.